Предмет: Алгебра,
автор: joni1234
Ответы
Автор ответа:
1
16х²-9у² : 8х+6у =(4х-3у)(4х+3у) * х = 4х-3у =
х² х х² 2(4х+3у) 2х
=4х - 3у = 2 - 3у = 2- 3*√50 =2 - 3*√25*√2 =2 - 3*5 =2- 15 =16-15 = 1
2х 2х 2х 2*√32 2*√16*√2 2*4 8 8 8
х² х х² 2(4х+3у) 2х
=4х - 3у = 2 - 3у = 2- 3*√50 =2 - 3*√25*√2 =2 - 3*5 =2- 15 =16-15 = 1
2х 2х 2х 2*√32 2*√16*√2 2*4 8 8 8
Похожие вопросы
Предмет: Математика,
автор: senkin2006
Предмет: Литература,
автор: khv5
Предмет: Литература,
автор: Miver675
Предмет: Математика,
автор: darpon2006
Предмет: Математика,
автор: tiktak12324